SOCIAL DIMENSIONS OF IBADAH IN THE QUR’AN - Mahfudz, Muhsin (Jurnal Diskursus Islam, 2022)
This article discusses the social dimensions contained in the Qur'an, especially verses that use the term ibadah (worship) in its various derivations. The discussion aims to unravel the ambiguity of meaning in society about whether ibadah only refers to the pure rituals (ibādah mahḍah) such as prayer or includes pious activities outside of pure rituals? In its analysis, this article uses the Tafsīr Mauḍū‘ī method, a method of interpretation that examines the concept of ibadah through the elaboration of the entire verse that uses the term. The analytical tools are textual and cultural analysis techniques that highlighted through a sociological approach, especially Max Weber's theory of beliefs about the influence of social behavior. The analysis results show that all verses that use the term ibadah in their various derivations are generally related to social dimensions. If there is a command to worship Allah, then the verses of the Qur'an are also with zakat and social security. By looking up to the characteristics of verses in the Qur'an, Max Weber's theory can be developed even though with different variables.